AJARAN DHARMA DALAM TEKS YAKṢA PRAŚNA - I Komang Dedi Diana; I Putu Ariyasa Darmawan (Jnanasidanta, 2019)
The Yakṣa Praśna as part of Itihāsa Mahābhārata is a dialogue between Yudhṣṭhira and the Yakṣa by the lake about the virtues of the Vedas, honesty, knowledge, and respect for parents. The Yakṣa is Lord Dharma who wants to test Yudhṣṭhira's abilities. Yudhṣṭhira placed the Vedas as the basic guidelines in his life, and positioned the people who controlled the Vedas as the main people and ignorance when humans did not know the Vedas. Some of the Yakṣa questions are answered by placing the Vedas as the answers.Yakṣa Praśna teaches humans to always act on truth, honesty, according to rules, and for happiness in the world and after death.The highest Dharma is to do good to all people, the dharma done according to the instructions of the Vedic scriptures always brings results, dengan mengendalikan pikiran, someone is never afraid, and union with goodness is never broken. Keyword: Dharma, Veda, Yudhṣṭhira, Yakṣa Praśna